PENGARUH BRAND EQUITYTERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA MISTER BURGER PURWOREJO (STIE Rajawali Purworejo, 2018)
This study aims to determine how the influence of brand equity on consumer purchasing decisions on Mister Burger Purworejo. This research uses quantitative approach, where data and information are collected through survey with questionnaire tool and also library study. The population of this study is consumers who have made purchases of products on Mister Burger Purworejo more than 2 times. The sample in this study amounted to 50 people. Data analysis technique used is multiple linear regression, coefficient of determination test, t test and F. test of multiple regression calculation obtained regression equation Y = 1,500 + 0,198X1 + 0,204 X2 + 0,513 X3. This means that, if the value of the brand awareness variable, brand association and brand quality perceptions in the research object is equal to zero, then the level or amount of purchase decision variables in Mister Burger Purworejo will be 1,500. The result of the determination coefficient hypothesis Adjust R Squaresebesar 0.734, that the variable purchase decision 73,4% influenced by brand awareness variable (X1), brand association (X2), and brand quality perception (X3). While 26.6% influenced by other variables. It can be concluded that partially there is a positive and significant influence between brand awareness, brand association and brand quality perceptions of consumer purchasing decisions. And simultaneously there is a positive and significant influence between the brand awareness variable, brand association and brand quality perceptions of purchasing decisions.